Phenolics from Brazilian propolis - Boudourova-Krasteva, G.; Bankova, Vassya; Sforcin, J. M. [UNESP]; Nikolova, N.; Popov, S. (My University, 1997)
The main phenolic constituents from Brazilian propolis, originating from Sao Paulo State, were isolated and identified: three flavonoids, a prenylated coumaric acid and two new benzopyranes, E and Z 2,2-dimethyl-6-carboxyethenyl-8-prenyl-2H-benzopyranes.
Keywords: Benzopyranes; Flavonoids; Phenolics; Propoils